Perception regarding reproductive health among adolescents of rural Sindh, Pakistan - Shahid, Anjum; Pirzada, Abdul Ghaffar; Memon, Ashfaque Ahmed (South East Asia Journal of Public Health, 2013)
Adolescence, the second decade of life, is a period in which an individual undergoes major physical and psychological changes. Adolescence is a period when health problems that have serious immediate consequences can occur or when problem behaviours that could have serious adverse effects on health in the future are initiated. This study examines the knowledge and perception regarding reproductive health and opinion toward reproductive health education among adolescents of rural Sindh, Pakistan. Study was conducted in 2008- 2009 on a total number of 369 adolescent males (209) and females (160) studying in colleges of Kambar Shadadkot, rural Sindh. This descriptive study using cluster sampling technique was conducted in randomly selected eight intermediate colleges of boys and girls. After informed consent and ensuring confidentiality, an anonymous quantitative questionnaire was completed to ascertain the knowledge of adolescents. Main outcome measures were adolescents knowledge of reproductive health concepts, pregnancy and contraceptive methods and knowledge in relation to sexually transmitted diseases (STDs) and HIV/AIDS. Analysis of data revealed that a sizable proportion of adolescents had low knowledge regarding reproductive health issues and had misconception regarding reproductive physiology, STDs and condoms. Teacher was the focal source of information and 63% male and 43 % female respondents desired a need for RH education. More than half of participants had no knowledge on STDs and HIV/AIDS and its spread and a small percentage had awareness regarding contraceptive methods, about condom use and its protective coverage against STDs and pregnancy. Strong efforts are needed to augment awareness among rural adolescents and education could serve the purpose. Gender-based ethnically amenable sex education curriculum should be introduced in educational institutions. South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 39-45 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15264